Right adrenal gland prospective evaluation through transgastric endoscopic ultrasound: an alternative approach - Figueiredo, Pedro C.; Pinto-Marques, Pedro; Almeida, Ines; Gomes, Pedro C.; Serra, David (Endoscopy International Open, 2016)
Background and aims: Endoscopic ultrasound (EUS) guided right adrenal gland (RAG) evaluation is frequently unsuccessful and, when feasible, requires a cumbersome maneuver through the duodenum. In our experience, the use of a recent ultrasound platform has enabled transgastric detection of the RAG with a simple maneuver. The aim of this study was to determine the RAG transgastric EUS detection rate and identify predictive factors for failure.Methods: Consecutive patients referred to EUS in a single center were prospectively included over a 6-month period. Success was defined as RAG transgastric EUS detection within 180 seconds. Logistic regression analysis was used to assess factors associated with failure. Results: Among 100 patients, the success rate for RAG transgastric EUS detection was 75 %, with a median maneuver duration of 45 seconds [interquartile range, 25 – 70 seconds]. Two incidental RAG lesions were detected. Of possible demographic and anthropometric predictive factors for failure, only age (OR 1.04; P = 0.04) was statistically significant on multivariate analysis. Conclusions: The transgastric EUS approach for RAG detection is simple, fast and effective.